Prophylactic fibulotomy during external fixation for tibia fractures: a retrospective study on reducing nonunion incidence - Agwulonu, Ifeanyi; Idowu, Oluwaseyi; Igbinba, Bright; Olusunmade, Opeyemi (International Journal of Research in Medical Sciences, 2025)
Background: Tibial fractures are prevalent long bone injuries that can result in nonunion, especially when treated with external fixation. Prophylactic fibulotomy has been suggested to improve fracture healing. This study evaluates the effectiveness of prophylactic fibulotomy in reducing nonunion rates in patients undergoing external fixation for tibial fractures. Methods: A retrospective cohort study was conducted at the National Orthopaedic Hospital, Igbobi, Lagos, Nigeria, analyzing patient records from January 2022 to December 2024. Associations between prophylactic fibulotomy and postoperative complications were assessed using chi-square tests, while t-tests compared time to union between fibulotomy and non-fibulotomy groups. A p value of less than 0.05 was considered statistically significant. Results: The study included 60 patients, predominantly males (53.3%) aged 40 years and above (58.3%). Distal fractures were most common (36.7%). Union was achieved in 70.0% of cases, with a significant association between fibulotomy and union status (χ²=18.367, p<0.005). The mean time to union was 15.8±1.4 weeks for patients who underwent fibulotomy, compared to 18.2±1.8 weeks for those who did not, indicating a significant difference (t=-5.179, p<0.05). Conclusions: Prophylactic fibulotomy during external fixation of tibial fractures is associated with higher union rates and shorter time to union, suggesting it may be a beneficial adjunctive procedure in managing tibial fractures requiring external fixation.